Network Coding versus Replication Based Resilient Techniques to Mitigate Insider Attacks for Smart Metering. (21st June 2015) - Brunisholz, Pierre; Erdene-Ochir, Ochirkhand; Abdallah, Mohamed; Qaraqe, Khalid; Minier, Marine; Valois, Fabrice
The main focus of this paper is the resilience of communication protocols for data gathering in distributed, large scale, and dense networks. In our previous work, we have proposed the resilient methods based on random behavior and data replications to improve route diversification, thus to take advantage of redundant network structure. Following these previous methods, we propose in this paper a new resilient method based on network coding techniques to improve resilience in Wireless Sensor Networks (WSNs) for smart metering applications. More precisely, using our resilience metric based on a performance surface, we compare several variants of a well-known gradient based routing protocol with the previous methods (random routing and packet replications) and the new proposed methods (two network coding techniques). The proposed methods outperformed the previous methods in terms of data delivery success even in the presence of high attack intensity.